Advances in the technology of managing people : contemporary issues in business - Gordon, Pamela Ann; Overbey, Julie A. (Emerald Publishing Limited, 2019)
Advances in the Technology of Managing People: Contemporary Issues in Business presents a wide ranging examination of emerging technological trends in the workplace. Using a combination of research study results, case studies, literature reviews, and conceptual papers, the book examines contemporary issues and emerging trends within management technology.Each chapter focuses on a different technological issue or trend within business management from a variety of perspectives, including management, HR, ethical, and organizational behavior viewpoints. Issues explored in the book include: Workplace Productivity with Balanced Scorecard Actions; Managing Emerging Technology and Organization with Agility; Freelance Economy; E-Mentoring 2.0; Virtual Team Success with the Power of Technology Advancements; Advanced Analytics, Machine Learning and Artificial Intelligence in the Workplace; Ambient Intelligence Changes the Office Environment; Disruptive Innovations and Blockchain; Quantum Leadership. Pamela Ann Gordon and Julie A Overbey curate an excellent reference for research scholars, practitioners, and organizational leaders seeking to understand the impact of technology on contemporary organizations.
Prelims -- Chapter 1: Technology and globalization: the evolution of human interactions, values, and management practices -- Chapter 2: Advances in information technology integrated with strategic direction -- Chapter 3: Advancing technologies in human resource development (HRD) -- Chapter 4: Employee engagement in 3D virtual learning environments: a digitized HRD framework model for leadership and learning -- Chapter 5: Advanced information technology: improve workplace productivity with balanced scorecard actions -- Chapter 6: Managing emerging technology and organizations with agility -- Chapter 7: The long tail of Generation Z and the future of a freelance economy -- Chapter 8: E-mentoring 2.0: changing the workplace through technology -- Chapter 9: Virtual team success with the power of technology advancements -- Chapter 10 Managing technology implementation change in a Caribbean organization -- Chapter 11 Technological work environments: issues in the government sector -- Chapter 12 Issues and advantages of advanced analytics, machine learning, and artificial intelligence in the workplace -- Chapter 13 Ambient intelligence changes the office environment -- Chapter 14 Disruptive innovations: blockchain and spinoffs -- Chapter 15 Quantum leadership: transmuting technology -- Chapter 16 The impact of quantum teleportation on business ethics -- Index.
Includes index.
Print version record.
Keywords: Industrial management -- Technological innovations; Leadership; Business & Economics -- Management; Business & management